Homogenization of the Freshwater Fish Fauna of the Biogeographic Regions of Chile - Castro-Morales, S (Elsevier B.V., 2019)
Studies at local and global scales have showed that fish freshwater communities are going through a process of biotic homogenization, due mainly to exotic species introduced from other regions, and to the extinctions or extirpations of native species. Here we analyze the compositional changes among the contiguous biogeographic regions of continental Chile, expecting an important homogenization for being contiguous. By means of the spatial turnover (βsim index), we determined the patterns of the compositional change and biotic homogenization from “historical” (βsim,H; calculated before the introduction of exotic species by post-European colonization) to “current” (βsim,C; calculated after the introduction of exotic species carried out by European colonizers) time. The differential turnover (Δβsim) exhibited an average of −0.04 and showing a significant distribution, with a median different from zero (P < 0.05). Our results indicate the regions are currently in an important homogenization process in comparison to those observed in studies between non-contiguous regions. This change is being influenced largely by the presence of exotic species and not by extirpations of native species affecting negatively the biosingularity of regions with a high degree of endemism. © 2019